2012
DOI: 10.5430/ijhe.v1n1p32
|View full text |Cite
|
Sign up to set email alerts
|

What Influences Implementation Intentions in an Academic Learning Context – The roles of Goal Intentions, Procrastination, and Experience

Abstract: Studies show that many students struggle with properly organizing their academic activities; what makes things even worse is that up to 90% of students are at least part-time procrastinators. In order to clarify how these students could be supported, the article at hand deals with the influences and possible benefits of implementation intentions in an academic learning context and substantiates the literature discussion with data collected among students. Aiming at studying the antecedents of academic performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 109 publications
0
14
0
2
Order By: Relevance
“…As I have previously discussed (e.g. Sommer, 2011;Sommer & Haug, 2012), two aspects are included implicitly in the TPB model that could contribute to reducing the intentionbehavior gap: (1) On the one hand, there is implementation intention, as discussed above, provided that intention is subdivided into goal intention and implementation intention, as proposed by Gollwitzer (1999); (2) On the other hand, there is experience which in the model above only has the influence of a background factor (Ajzen, 2005). Implementation intention as an approach to reduce the gap was examined by Ajzen (2005) for example in connection with literal inconsistencies: "perhaps consistent with this account, implementation intentions may be effective because they improve memory for the behavioral intention" (Ajzen, 2005, p. 106).…”
Section: Theory Of Planned Behavior -Implementation Intention and Expmentioning
confidence: 90%
See 3 more Smart Citations
“…As I have previously discussed (e.g. Sommer, 2011;Sommer & Haug, 2012), two aspects are included implicitly in the TPB model that could contribute to reducing the intentionbehavior gap: (1) On the one hand, there is implementation intention, as discussed above, provided that intention is subdivided into goal intention and implementation intention, as proposed by Gollwitzer (1999); (2) On the other hand, there is experience which in the model above only has the influence of a background factor (Ajzen, 2005). Implementation intention as an approach to reduce the gap was examined by Ajzen (2005) for example in connection with literal inconsistencies: "perhaps consistent with this account, implementation intentions may be effective because they improve memory for the behavioral intention" (Ajzen, 2005, p. 106).…”
Section: Theory Of Planned Behavior -Implementation Intention and Expmentioning
confidence: 90%
“…Current studies like the one by Coté, Gagon, Kouffé Houme, Abdeljelil and Gagon (2012), too, confirm the relevance of past behavior. However, these studies are in conflict with numerous oppositional studies that notably question the relevance of past behavior and/or experience (Sommer, 2011;Sommer & Haug, 2012). In the context of the TPB model experience is classified explicitly as background factor (Ajzen, 2005).…”
Section: Theory Of Planned Behavior -Implementation Intention and Expmentioning
confidence: 98%
See 2 more Smart Citations
“…Subjective Norm Subjective norm is described as "perceiving social pressure whether to perform or not to perform the specific behavior" (i.e., social entrepreneurship) (Kautonen, van Gelderen, & Fink, 2015; Kautonen, van Gelderen, & Tornikoski, 2013; Ajzen, 1991). Preceding research observed a robust linkage between norm and intention (Ajzen, 1991;Fishbein & Ajzen, 1975 (Sommer & Haug, 2011). Some researchers have concluded that subjective norms are strongly dependent on context (Hübner & Kaiser, 2006).…”
Section: Ementioning
confidence: 99%